OPERATIONAL AUDITING -THE EXTENSION OF THE INTERNAL AUDIT - Yakubov Matrasul Mavlonberdiyevich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The operational audit can be a valuable tool in the managementinformation system of an organization. Efficient management is a key toany company’s success. Checking and improving the management can beaccomplished through the operational audit. In this article, described the nature of operation audit and the process of conducting it by internal auditor. Moreover, defined the difference of financial and operational audit.